2020
DOI: 10.21608/besps.2020.27043.1049
|View full text |Cite
|
Sign up to set email alerts
|

Do Sofosbuvir and Daclatasvir Affect Vitamin D and Iron Status in Chronic Hepatitis C Virus Patients? Role of Hepcidin

Abstract: Aim: This study was designed to assess the impact of sofosbuvir/daclatasvir on vitamin D and iron status in chronic HCV patients (CHC). Methods: Sixty-five CHC patients registered for sofosbuvir/daclatasvir based regimen were recruited. Serum vitamin D, total iron, total iron binding capacity, and serum hepcidin were measured prior the treatment and 12 weeks after the stoppage of the treatment. Transferrin saturation was calculated. Results: The present study showed that a great majority of CHC patients had vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a parallel line, Abd Allah et al reported that CHC is associated with vitamin D deficiency but iron overload, resulting in a reduced level of hepcidin. Treatment with sofosbuvir/daclatasvir increases hepcidin, thereby reducing iron levels and increasing vit D [ 85 ]. A study by [ 19 ] showed that vit D reduces HCV protein production in cell culture synergistically with IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel line, Abd Allah et al reported that CHC is associated with vitamin D deficiency but iron overload, resulting in a reduced level of hepcidin. Treatment with sofosbuvir/daclatasvir increases hepcidin, thereby reducing iron levels and increasing vit D [ 85 ]. A study by [ 19 ] showed that vit D reduces HCV protein production in cell culture synergistically with IFN-α.…”
Section: Discussionmentioning
confidence: 99%